The effect of triple reuptake inhibitor toludesvenlafaxine on neurological function in cerebral ischemic rats - Sun, Xiaohui; Wang, Tian; Zhou, Lin; Zhang, Ce; Fu, Fenghua (Frontiers in Pharmacology, 2023)
Purpose: The aim is to investigate the effect of toludesvenlafaxine (Tdv), a reuptake inhibitor of serotonin, norepinephrine, and dopamine, on the neuroprotective effects in cerebral ischemic rats and the underlying mechanisms. Material and Methods: Middle cerebral artery occlusion/reperfusion (MCAO/R) model was induced in rats and the neuroprotective effects of Tdv were evaluated by infarct size, Garcia test, and beam walking test. Neuronal apoptosis in the peri-infarct area was observed by TUNEL staining. And the apoptosis-related proteins were evaluated with Western blotting. The role of CREB pathway in effect of Tdv was also investigated using Western blotting and immunofluorescence. Results: In the MCAO/R model, administration of Tdv reduced the infarct size, promoted neural functional recovery, decreased the expression of Bax and Caspase-3, and increased the expression of Bcl-2 and BDNF. In addition, Tdv reduced neuronal apoptosis in the peri-infarct area. Tdv increased the expression of phosphorylated CREB. The application of the specific CREB inhibitor, compound 666-15, could effectively reverse the anti-ischemic cerebral injury of Tdv in MCAO/R rats. Conclusion: Tdv ameliorated cerebral ischemic injury through reducing neuronal apoptosis and increasing the expression of BDNF partly via the activation of CREB pathway.